Design of robust power system stabilizers for Iraqi power network - Almurib, H.A.F.; Hassan, L.H.; Moghavvemi, M. (2011)
In this paper, Genetic Algorithms is applied to find out the number of PSSs and to optimize their parameters and locations under different operating conditions for Iraqi power network. The problem is formulated as an optimization problem to maximize the minimum damping ratio of the electromechanical modes using different number of PSSs. The robustness and effectiveness of the proposed approach is approved in damping of electromechanical modes of oscillations using Eigenvalues analysis and nonlinear simulation results.